The Invisible Revolution: The Future of Wearable Health Technology Beyond Smartwatches - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The global health technology landscape is undergoing a profound transformation, driven by the convergence of advanced sensor technology, big data analytics, ...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics